KINERJA DOSEN: KONTRIBUSINYA TERHADAP AKREDITASI PERGURUAN TINGGI - Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Being a good lecturer is awareness, but being a responsible lecturer is a demand. In this section, it will be found that many lecturers are not correct in some of their obligations, and this causes the institution's performance to be drop. In this research, it will be stated how the actual lecturer performance, what is the meaning and impact, and what to do next. Qualitative methods are used to see the reality of a phenomenon, and the data becomes authentic evidence, so that it can be suggested implications. The results showed that the lecturers' performance was low, both in education, research, and community service. This emphasizes how lecturers are ignorant of their obligations, how institutional leaders do not care about the situation, and this is normal if the institution's achievement is low